REPRESENTASI KRITIK BERBAHASA MELAYU TENTANG KABUT ASAP PADA POJOK ATAN SENGAT DI HARIAN PAGI RIAU POS - Rahmawati, Yuni; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Smog occurred in Riau every year. The smog in 2015 became the longest event and very severe compared with previous years. This is the media attention, especially Riau Pos which is the largest newspaper in Riau. Atan Sengat’s cartoon the mascot of Riau Pos which has been criticized about haze associated with his trademark use of the Malay language and say what it is. Therefore, this study aims to determine the meaning contained in the criticism of Malay Language in the Pojok Atan Sengat and ideologies of the Riau Pos associated haze in Riau during June to September 2015.Method of this research is qualitative research method with semiotic approach. Data collection techniques that interview and documentation. Data were analyzed using analysis of Roland Barthes Semiotics. The unit of data analysis in this research consist of Pojok Atan Sengat of the criticism about the news of smog that contained the main page of Riau Pos from June to September 2015.The results show: first, at the time of the occurrence of smog, Atan Sengat is positioning itself as the people of Riau are also feeling the effects of smog. No matter that it attracted Atan Sengat of the measures that have been taken by the government while suffering because of the haze is still felt as the people of Riau. So Atan Sengat can easily attract the attention of the public and are considered to represent the feeling of the people of Riau during the occurrence of haze in Riau. Second, ideology of Riau Pos is capable to providing the information required by the about haze to the reader. For Riau Pos, news of smog is considered something very important, related to the latest weather conditions and information from the parties that handle (Government, BMKG, BNPB). Pojok Atan Sengat, comments written by Riau Pos relating to the headlines. However, Atan Sengat is not entirely pro to the headline news. Atan Sengat is precisely to comment in accordance with people's perceived reality Riau. Riau Pos give responsible freedom in the character of the Atan Sengat.